Phenylpropanoid-specific glycosyltransferases from mango and their potential role in defense - Vare, Tejas; Joshi, Rakesh; Liao, Jieren; Hoffmann, Thomas; Schwab, Wilfried; Giri, Ashok (Plant Physiology and Biochemistry, 2026)
Alphonso mango (Mangifera indica cv. Alphonso) is a cornerstone of India's fruit industry due to its distinct aroma and shelf-life characteristics. The uridine diphosphate-dependent glycosyltransferases (UGTs) play a crucial role in stabilising aroma and defense-related specialised metabolites in fruits. The present study explores the potential role of UGTs during mango ripening and Colletotrichum gloeosporioides infection. Gene expression analysis indicated that UGTs showed dynamic expression in skin and pulp during ripening. Phylogenetic analysis revealed substrate-driven divergence of UGTs, with MiUGT92A14 and MiUGT95B15 forming distinct clades associated with flavonoid glycosylation. Recombinant UGTs showed a higher preference for UDP-glucose, which is corroborated by the high accumulation of UDP-glucose during ripening. Furthermore, it was observed that MiUGT92A14 prefers phenolic acids as substrates, while MiGT95B15 shows flavonoid specificity. Spore germination assays demonstrated that both aglycones and their glycosylated derivatives suppressed early fungal morphogenesis, supporting a role for UGT-mediated glycosylation in maintaining defense-related metabolites in a bioactive yet non-toxic form during fruit ripening. Additionally, Colletotrichum gloeosporioides inhibition assays demonstrated that glycosylated products of selected UGTs exhibited equal or enhanced antifungal activity compared with their aglycone forms, indicating that glycosylation promotes the safe accumulation of antifungal compounds by reducing aglycone toxicity to the plant. These findings suggest that glycosylation of specific metabolites is a key for ripening process and to potentiate defence against fungal pathogen.
Keywords: Anthracnose; defense; Flavonoid; Glycoconjugates; Uridine diphosphate-dependent glycosyl-transferase